What can history reveal about the future of Sino-American relations?—Retrospect, reflections, and prospects. Issue 1 (2nd January 2021) - Lixin, Wang
Abstract: Over the past two centuries, U.S.-China relations have undergone a historical evolution from friendship to hostility and then from hostility to cooperation, and are now at a crossroads from cooperation to confrontation. History has shown that U.S.-China relations are extremely important to China, affecting not only China's overall national security environment, but even largely determining the success or failure of China's modernization and directly relating to the well-being of ordinary Chinese people. Compared with other bilateral relations, U.S.-China relations are full of strong emotions and deeply influenced by ideology, and have great peculiarities. China should learn from the experience and lessons of history and open up a new future for U.S.-China relations by promoting a new round of greater Reform and Opening up, repositioning China's position in the world, and reducing the propaganda of the "China model" and "Chinese Road" to prevent the two countries from entering a "new Cold War."